Etic and Emic Perspectives on the Notopē Lolos Post-Marriage Tradition in Madura - Masrufah; Abdul Jalil; Akhtiar, Muhammad Najid (Fakultas Syariah IAIN Madura, 2025)
The Notopē Lolos tradition serves as a vital mechanism in maintaining harmony, building social legitimacy, and strengthening cultural identity in Madurese society. This tradition is not only a ritual but also a symbolic and social structure with meaning and values. Therefore, the emic and etic approaches become essential in deeply and contextually explaining how a culture is understood. This research is an empirical study using an anthropological approach. It aims to examine the cultural study of the Notopē Lolos tradition after marriage in Madura, the local wisdom values embedded within it, and its implications for family harmony in Madura. The findings show that by employing both emic and etic approaches within an anthropological framework, this study presents a comprehensive understanding of the Notopē Lolos tradition as a social institution that plays a crucial role in the kinship structure of Madurese society. The local wisdom manifested in this tradition not only strengthens cultural identity but also preserves social stability and harmony among individuals and families within the community. The Notopē Lolos tradition significantly contributes to family harmony in Madura, particularly when understood and practiced based on its underlying values. Therefore, Notopē Lolos endures not merely as a cultural heritage but also as a functional social instrument for maintaining family harmony.